Stimulus modality, perceptual overlap, and the go/no-go N2. - Nieuwenhuis, S; Yeung, N; Cohen, J (2004)
Stimuli that elicit a prepotent but incorrect response are typically associated with an enhanced electrophysiological N2 that is thought to index the operation of a control process such as inhibition or conflict detection. However, recent studies reporting the absence of the N2 modulation in go/no-go tasks involving auditory stimuli challenge this view: It is not clear why inhibition or conflict detection should be sensitive to the modality of the stimulus. Here we present electrophysiological data from a go/no-go task suggesting that the relative size of the N2 modulation in visual and auditory tasks depends on the perceptual overlap between the go and no-go stimuli. Stimuli that looked similar but sounded different were associated with a typical visual N2 modulation and the absence of an auditory N2 modulation, consistent with previous findings. However, when we increased the perceptual overlap between the auditory stimuli, a large no-go N2 was observed. These findings are discussed in terms of existing hypotheses of the N2, and clarify why previous studies have not found an N2 modulation in auditory go/no-go tasks.